Comparative electron irradiations of amorphous and crystalline astrophysical ice analogues. Issue 18 (25th April 2022) - Mifsud, Duncan V.; Hailey, Perry A.; Herczku, Péter; Sulik, Béla; Juhász, Zoltán; Kovács, Sándor T. S.; Kaňuchová, Zuzana; Ioppolo, Sergio; McCullough, Robert W.; Paripás, Béla; Mason, Nigel J.
Abstract : We have irradiated the amorphous and crystalline phases of CH3 OH and N2 O astrophysical ice analogues using 2 keV electrons and have found that the decay rate is dependent upon the nature and extent of the intermolecular bonding in these solid phases. Abstract : Laboratory studies of the radiation chemistry occurring in astrophysical ices have demonstrated the dependence of this chemistry on a number of experimental parameters. One experimental parameter which has received significantly less attention is that of the phase of the solid ice under investigation. In this present study, we have performed systematic 2 keV electron irradiations of the amorphous and crystalline phases of pure CH3 OH and N2 O astrophysical ice analogues. Radiation-induced decay of these ices and the concomitant formation of products were monitored in situ using FT-IR spectroscopy. A direct comparison between the irradiated amorphous and crystalline CH3 OH ices revealed a more rapid decay of the former compared to the latter. Interestingly, a significantly lesser difference was observed when comparing the decay rates of the amorphous and crystalline N2 O ices. These observations have been rationalised in terms of the strength and extent of the intermolecular forces present in each ice. The strong and extensive hydrogen-bonding network that exists in crystalline CH3 OH (but not in the amorphous phase) is suggested to significantly stabilise this phase against radiation-induced decay. Conversely, although alignment of the dipole moment of N2 O is anticipated to be more extensive in the crystalline structure, its weak attractive potential does not significantly stabilise the crystalline phase against radiation-induced decay, hence explaining the smaller difference in decay rates between the amorphous and crystalline phases of N2 O compared to those of CH3 OH. Our results are relevant to the astrochemistry of interstellar ices and icy Solar System objects, which may experience phase changes due to thermally-induced crystallisation or space radiation-induced amorphisation.